1991
DOI: 10.1055/s-0038-1646416
|View full text |Cite
|
Sign up to set email alerts
|

125I-Fibrinogen Binding to Platelets in Myeloproliferative Disease

Abstract: SummaryRecent reports have suggested a variation in the density and affinity of fibrinogen binding sites in platelets from patients with myeloproliferative disorders (MPD) which may reflect platelet functional abnormalities in these subjects. We have investigated the binding of 125I-fibrinogen (125I-Fb) to gel-filtered platelets from a large relatively homogeneous group of patients with MPD compared to normal age matched controls. Twenty-two of the patients investigated had polycythaemia vera and four essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…We have shown that the EC50 for added fibrinogen supporting ADP induced aggregation in this way is approximately 60 mm which is very similar to the Kd for [1251]-fibrinogen binding in the presence of ADP to the high affinity binding site (70 nM) in the same platelets (Mistry et al, 1991). Several groups of workers have examined the density and affinity of fibrinogen binding sites on abnormal platelets from patients with myeloproliferative disorders (MPD) in an attempt to relate changes in this receptor to clinical abnormalities (Clezardin et al, 1985;Landolfi et al, 1988;Mazzucato et al, 1989;Mistry et al, 1991). These studies show conflicting results indicating a pathological correlation depending on whether high or low affinity binding is considered.…”
Section: (Iii) Measurement and Characterisationsupporting
confidence: 56%
See 2 more Smart Citations
“…We have shown that the EC50 for added fibrinogen supporting ADP induced aggregation in this way is approximately 60 mm which is very similar to the Kd for [1251]-fibrinogen binding in the presence of ADP to the high affinity binding site (70 nM) in the same platelets (Mistry et al, 1991). Several groups of workers have examined the density and affinity of fibrinogen binding sites on abnormal platelets from patients with myeloproliferative disorders (MPD) in an attempt to relate changes in this receptor to clinical abnormalities (Clezardin et al, 1985;Landolfi et al, 1988;Mazzucato et al, 1989;Mistry et al, 1991). These studies show conflicting results indicating a pathological correlation depending on whether high or low affinity binding is considered.…”
Section: (Iii) Measurement and Characterisationsupporting
confidence: 56%
“…In situ on the platelet the complex exhibits the properties of a membrane binding site in that binding of fibrinogen is saturable, reversible and dependent on the presence of divalent cations in physiological concentrations (Marguerie et al, 1979;Peerschke et al, 1980). The characterisation of receptor density (Bma,) and affinity (Kd) on platelets has been undertaken in a number of laboratories using radioligand binding methods Marguerie et al, 1987;Mistry et al, 1991;Peerschke et al, 1980). Briefly the technique involves the preparation of gel-filtered platelets from citrated/aspirin treated blood followed by stimulation with agonists (usually ADP and thrombin) in the presence of millimolar concentrations of divalent ions and varying quantities of the radioligand.…”
Section: (Iii) Measurement and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…96 Analysis of fibrinogen binding to platelets revealed a decreased number of binding sites in most stud ies. 94,97,98 Heterogeneous affinity of fibrinogen receptors was reported by Landolfi et al 97 in patients with PV and was attributed to platelet heterogeneity in this disease.…”
Section: Platelet Membrane Receptorsmentioning
confidence: 81%
“…Aggregation is mainly mediated through glycoprotein IIb/IIIa. Several authors have demonstrated that the glycoprotein IIb/IIIa complexes are decreased in patients with MPDs [9], in addition to a decrease in the binding of fibrinogen, which is the functional counterpart of decreased glycoprotein IIb/IIIa receptors on the platelet surface [9,10]. Some investigators demonstrated that MPD patients may not only have a quantitative decrease of glycoprotein IIb/IIIa receptors on the platelet surface, but also a qualitative defect [11].…”
Section: Discussionmentioning
confidence: 99%